Abraham model correlations for describing the solubilising character of 3-Methoxy-1-butanol and 1-tert-Butoxy-2-propanol solvents. (4th March 2019) - Hart, Erin; Jodray, Megan; Rodriguez, Karen; Barrera, Maribel; Qian, Ellen; Zha, Olivia; Tong, Xin Y.; Woods, Delani; Liu, Yuqing; Lee, Grace; Acree, William E.; Abraham, Michael H.
ABSTRACT: Experimental solubilities are measured for 18 crystalline organic nonelectrolyte solutes dissolved in 3-methoxy-1-butanol and for 23 crystalline organic nonelectrolyte solutes dissolved in 1- tert -butoxy-2-propanol. The measured experimental data, combined with published literature data, are used to determine Abraham model correlations for the two alkoxyalcohol solvents. The derived Abraham model correlations back-calculated the observed solubilities to within 0.12 log units.